Pembelajaran Bahasa Arab Di Sekolah Islam Berbasis Boarding School - Mirza Mahfud; Marsiah Marsiah; Nur Fuadi Rahman; Nurul Wahdah (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2023)
The purpose of this study was to find out the learning of Arabic at SMP IT Hasanka Boarding School and to find out the factors that influence learning Arabic at SMP IT Hasanka Boarding School. This research uses a qualitative approach with the type of field research conducted at SMP IT Hasanka Boarding School and Hasanka Boarding School Dormitory by using qualitative data analysis. Methods of data collection obtained from observation, interviews, and documentation. The results showed that learning Arabic in Islamic schools based on boarding school at SMP IT Hasanka Boarding School, namely learning Arabic in two models, namely learning in class and learning in the dormitory. For learning in class, the objectives, approaches, models, methods, media, materials and evaluation are different from learning in dormitories, not only different from learning in dormitories but also different from other regular schools. As for the factors that influence Arabic Language Learning in Boarding School-Based Islamic Schools at SMP IT Hasanka Boarding School, namely internal and external factors, internal factors are those that come from within the student such as the student's condition, and how students pay attention to learning Arabic. While external factors, namely those that come from outside the student's self that are considered by researchers such as: teachers, methods, media and infrastructure, as well as the social environment towards learning Arabic.